Estudo biomonitorado do extrato da folha da Euphorbia umbellata (Pax) Bruyns para a proposta de formação de nanopartículas de prata contendo ativos vegetais com potencial biológico. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
The use of natural products both for the prevention and treatment of diseases is something very old and often carried out empirically by the population. As an example, we can highlight the popular use of extracts of Euphorbia umbellata (Pax) Bruyns, popularly known as janaúba, blind-eye or glue-note, which is used for the treatment of cancer, gastric ulcer, inflammatory processes and other diseases. . In the same sense, there are few studies that evaluate nanostructured systems containing substances present in plant extracts with medicinal potential; as silver nanoparticles (obtained by the green synthesis process). This work proposes a qualitative-quantitative evaluation of the main plant metabolites present in extracts obtained from E. umbellata leaves and a biomonitored study against lung cancer cell lines (A549 and H292) and strains of microorganisms (Klebsiella pneumoniae, Pseudomonas aeruginosa and Staphylococcus aureus), seeking to identify the most active extracts that can be used in the development of silver nanoparticles. After obtaining the nanoparticles prepared from the most active extracts, it is proposed to evaluate physicochemically these systems and the therapeutic potential against the evaluation models of cytotoxicity and antimicrobial activity. Thus, secondary metabolites such as tannins, flavonoids, alkaloids and terpenes were identified in the evaluated extracts. The quantification of terpenes was performed in the 5 extracts, the hexane fraction had the highest concentration (7.24 mg of eufol/g of extract) and the aqueous extract had the lowest concentration of terpenes (0.20 mg of eufol/g of extract). The dichloromethane and hexane extracts showed the best results for the minimum inhibitory concentration. The evaluation of cytotoxicity against the A549 strain showed that the hexane and dichloromethane extracts were the most active, with IC50 of 5.28 ± 1.40 and 2.74 ± 0.89 respectively. For H292 cells, the dichloromethane extract was the most active with IC50 of 27.52 ± 7.43. The hexane and dichloromethane extracts were used in the development of silver nanoparticles. Visual analysis of the samples and evaluation using UV-vis spectrometry showed that silver nanoparticles were formed after 35 minutes of exposure to artificial light (for both extracts). The nanoparticles obtained had an average size of 166.9 ± 1.3 nm and 277.8 ± 1.4 mm, a polydispersity index of 0.405 ± 2.3 and 0.422 ± 1.8, and a zeta potential of -30.5 ± 1.8 mV and -35.7 ± 1.4 mV, for hexane and dichloromethane extracts respectively. Dichloromethane nanoparticles were evaluated in microbiological and cytotoxicity tests. Dichloromethane nanoparticles at a concentration of 0.5 µg/mL inhibited the growth of Pseudomona aeruginosa by over 50%. This inhibition occurred at a concentration of 0.25 µg/mL for Staphylococcus aureus and 0.1 µg/mL for the bacterial strain Klebsiella pneumoniae. Regarding cytotoxicity, the nanoparticles showed much more satisfactory results when compared only with the use of the extract. With a concentration of 0.25 µg/mL there was a significant reduction in cell viability and for the H292 cell this reduction occurred at a concentration of 0.1 µg/mL. Therefore, the dichloromethane silver nanoparticles showed satisfactory results.
Keywords: Terpenos; Nanopartícula de prata; Síntese Verde; Câncer de pulmão; Ação Antimicrobiana; Terpenes; Silver Nanoparticles; Green Synthesis; Lung cancer; Antimicrobial Action; CNPQ::CIENCIAS BIOLOGICAS::FARMACOLOGIA::FARMACOLOGIA GERAL